SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PERSONIL DITRESKRIMSUS BERPRESTASI MENERAPKAN METODE VIKOR (STUDI KASUS: POLDA SUMUT) - Retnowati Sitanggang; Garuda Ginting (STMIK Budi Darma, 2018)
The North Sumatra Police Board award team headed by the Deputy Chief of Police conducted the election of Ditreskrimsus personnel each month by giving awards to personnel / apparatuses who had real and extraordinary achievements whose results could be proud of and beneficial for the advancement of institutional quality improvement. Decision support systems or often referred to as Multi Criteria Decision Making (MCDM) function to carry out the selection process and assist someone in making accurate and targeted decisions. One method in the MCDM is Vlsekriterijumska Opimizacija I Kompromisno Resenje (VIKOR). Where this method is used to select more than one criterion and has advantages in compromising existing alternatives, then the best results selection process will be carried out, and can complete discretionary decision making. The purpose of this study is to apply the VIKOR method in making decision-making decisions for outstanding personnel in Ditreskrimsus.Keywords: decision support system, ditreskrimsus, vikor